1964
DOI: 10.1039/jr9640004753
|View full text |Cite
|
Sign up to set email alerts
|

917. Heterocyclic organoboron compounds. Part II. Preparation and properties of 1-aza-5-boratricyclo[3,3,3,0]undecane and related compounds

Abstract: Hydroboronation. of the three double bonds in triallylamine yields a tricyclic compound (I) with bridgehead nitrogen and boron atoms and a direct B-N bond; it is an unreactive, volatile solid which hydrolyses slowly to dipropylaminopropylboronic acid (11) and tripropylamine. Hydroboronation of triallylborane yields the analogous bicyclic dibora-compound (IV) which is highly reactive and forms adducts with nitrogen donors.The infrared spectrum of azaboratricycloundecane is compared with those of triethanolamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
2

Year Published

1983
1983
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…(2) A. Greenberg and J. F. Liebman, "Strained Organic Molecules", Academic Press, New York, 1978. 0001-4842/83/0116-0321$01.50/0 © 1983 American Chemical Society Bicyclic systems built from medium rings have been mainly remarkable for their rarity! There are just 10 basic bicyclic systems containing only 8-to 11-membered rings: bicyclo [3.3.3]undecane, bicyclo [4.4.2]dodecane, bicyclo [4.3.3]dodecane, bicyclo [5.4.2]tridecane, bicyclo [5.3.3]tridecane, bicyclo [4.4.3]tridecane, bicyclo [6.3.3]tetradecane, bicyclo [5.4.3]tetradecane, bicyclo [4.4.4]tetradecane, and bicyclo [5.4.4]pentadecane.…”
mentioning
confidence: 99%
“…(2) A. Greenberg and J. F. Liebman, "Strained Organic Molecules", Academic Press, New York, 1978. 0001-4842/83/0116-0321$01.50/0 © 1983 American Chemical Society Bicyclic systems built from medium rings have been mainly remarkable for their rarity! There are just 10 basic bicyclic systems containing only 8-to 11-membered rings: bicyclo [3.3.3]undecane, bicyclo [4.4.2]dodecane, bicyclo [4.3.3]dodecane, bicyclo [5.4.2]tridecane, bicyclo [5.3.3]tridecane, bicyclo [4.4.3]tridecane, bicyclo [6.3.3]tetradecane, bicyclo [5.4.3]tetradecane, bicyclo [4.4.4]tetradecane, and bicyclo [5.4.4]pentadecane.…”
mentioning
confidence: 99%
“…Herein, we report the first demonstration of water-triggered dehydration and concomitant aggregation of water-dissolved polymers based on a hydrolysis reaction using the statistical copolymers of triethanolamine borate (TEAB) methacrylate and styrene (St). TEAB is a cage-shaped borate ester with internal N–B coordination and is called boratrane. We have previously found that TEAB-pendant statistical copolymers of St possess better affinity to polar solvents than their triethanolamine (TEA) counterparts, which is consistent with the dipole moments for pristine TEAB (8.8 D) and TEA (3.6 D) molecules. This unique polarity relationship inspired us to investigate whether the hydrolysis of TEAB can be applied to the water-triggered dehydration of water-dissolved molecules to induce spontaneous aggregation without any external stimuli.…”
mentioning
confidence: 64%
“…By contrast to the above organometallic macrocycles, organoboron macrocycles have remained extremely scarce, a situation that possibly reflects the inherent reactivity of these compounds toward water and oxygen. One of the earliest contributions in this field of research is a 1964 paper describing 1,5‐diborabicyclo[3,3,3]undecane ( 1 ) as a product of the reaction of triallylborane with Et 3 NBH 3 (Scheme ) 4. Although the synthesis of this compound was never reproduced and its properties were not experimentally explored, this early account inspired many researchers, thereby leading to isolation of organoboron macrocycles, such as 2 5 and 3 6.…”
Section: Methodsmentioning
confidence: 99%